2016
DOI: 10.1097/mao.0000000000001103
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transmastoid Surgery for Superior Semicircular Canal Dehiscence Syndrome

Abstract: Management strategies and surgical techniques continue to evolve for SSCDS. We currently offer transmastoid resurfacing having informed patients of a 25% possibility of incomplete symptom resolution, and explain that plugging can be performed as a "second stage," if necessary. However, as we accrue more experience and there is more evidence from the literature we are considering whether to offer transmastoid plugging as our primary surgical procedure. In our experience, patients with multiple vestibular pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 15 publications
2
22
2
1
Order By: Relevance
“…Several meta‐analyses have examined the surgical complications related to SSCD treatment. No significant differences in outcomes or complications were found between resurfacing and plugging, whether through a transmastoid or middle cranial fossa approach . Vestibular hypofunction was only seen in one of 12 (8%) ears in our study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Several meta‐analyses have examined the surgical complications related to SSCD treatment. No significant differences in outcomes or complications were found between resurfacing and plugging, whether through a transmastoid or middle cranial fossa approach . Vestibular hypofunction was only seen in one of 12 (8%) ears in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Most recently, Powell et al reported on their experience with transmastoid resurfacing with bone paté and fibrin sealant . Here, success was defined by an improvement in symptoms and quality of life, and the authors found significant improvements in 6 of 9 symptoms; most patients reported that the surgery improved their quality of life …”
Section: Introductionmentioning
confidence: 99%
“…Resurfacing material also varies and can include cartilage, fascia, bone dust, fibrin glue, and hydroxyapatite cement. The transmastoid approach to plugging the canal has also been used in many cases with excellent results (38, 9092). Prior to pursuing surgery, however, control of migraine is critical to avoid exacerbation of migraine after surgery and to distinguish treatable symptoms that are unlikely to be helped by repairing a dehiscence.…”
Section: Treatmentmentioning
confidence: 99%
“…We feel a significant disadvantage of the transmastoid approach is the lack of directly seeing the dehiscence, thereby risking inadequate plugging on either side of the dehiscence. Some have suggested this can be circumvented by elevating dura over the dehiscence via the mastoid and using a mirror to ensure the canal is adequately plugged (92). …”
Section: Treatmentmentioning
confidence: 99%
“…Early feasibility studies on hearing preservation after canal plugging were observed by Parnes and McClure among guinea pigs [Parnes and McClure, 1985]. Among human-beings, the preservation of hearing thresholds has been observed in patients undergoing canal plugging of the posterior canal through the transmastoid approach and the superior canal by the middle cranial fossa approach [Agrawal and Parnes, 2001;Banakis Hartl and Cass, 2018;Beyea et al, 2012;Lundy et al, 2011;Niesten et al, 2013;Powell et al, 2016;Van Haesendonck et al, 2016;Yamauchi et al, 2017] as well as the superior canal by middle cranial fossa approach [Ward et al, 2012]. Generally, surgery has a positive impact of the symptoms of SCDS.…”
Section: Introductionmentioning
confidence: 99%